2021
DOI: 10.1037/stl0000266
|View full text |Cite
|
Sign up to set email alerts
|

Improving university student course performance using reflective exam analysis: An approach to developing academic proficiency.

Abstract: Introductory psychology is a course that covers an extensive amount of content and often has a larger enrollment at universities that include it in their general education requirements, which can cause it to be a challenging course for many students (Homa, Teaching of Psychology, 2013, 40, p. 169). Research indicates that students need to engage in effective test-taking strategies and assess their deficiencies to be successful on exams (Fleming, Teaching of Psychology, 2002, 29, p. 115). One potential solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Exam-Wrappers have been shown to aid in the development of SRL strategies and contribute to students’ academic success ( 7 , 9 , 38 , 39 , 58 60 ). Specifically, Exam-Wrappers can help students reflect on preparation methods and assess factors contributing to their performance on assessments ( 38 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exam-Wrappers have been shown to aid in the development of SRL strategies and contribute to students’ academic success ( 7 , 9 , 38 , 39 , 58 60 ). Specifically, Exam-Wrappers can help students reflect on preparation methods and assess factors contributing to their performance on assessments ( 38 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stability of these scales was calculated using alpha kronbach coefficient, and half-segmentation. Their authenticity was calculated using link transactions, content reliability, and factor reliability only (Grewe et al, 2021;Hosseinpour et al, 2019).…”
Section: The Fourth Dimensionmentioning
confidence: 99%
“…Across a wide range of academic disciplines, we only identified five experiments with students fully randomized to an exam wrapper or comparison group, and only two of these studies showed a positive effect of using exam wrappers (Chen et al, 2017; Edlund, 2020), while the other three found no benefit (Chambers, 2020; Craig et al, 2016; Stephenson et al, 2017). There are also quasiexperimental studies of exam wrappers that vary in methodological rigor, and these too show mixed results (Grewe et al, 2021; Hodges et al, 2020; LaCaille et al, 2019; Rosales et al, 2019; Soicher & Gurung, 2017; Thompson, 2012). Moreover, the implementation of wrappers varies across studies—of the two fully randomized experiments that did find a benefit of exam wrappers, one used an exercise that focused on reflecting on previous performance and occurred close after an exam in a psychology course (Edlund, 2020), while the other focused on planning for future exams and occurred shortly before the next exam in a statistics class (Chen et al, 2017).…”
mentioning
confidence: 99%